The Effect Of Self Leadership And Organizational Commitment To Employee Performance At The Four Points By Sheraton Hotel - Aditya Darma Putra, I Made; Sintaasih, Desak Ketut (E-Jurnal Manajemen; Vol 7 No 8 (2018)DO - 10.24843/EJMUNUD.2018.v07.i08.p08, 2018)
Performance is the result of work achieved employee in a company how employees do the job. This study aims to determine the influence of self-leadership and organizational commitment to employee performance at Four Points by Sheraton Bali Hotel. Samples taken is 100 respondents, with nonprobability sampling method with accidental sampling technique. Data collection is done through observation, interview and questionnaire. The analysis technique used is multiple regression. The results showed that self leadership and organizational commitment partially and simultaneously have a positive and significant effect on employee performance. The result showed need to create an atmosphere or working conditions that can meet the expectations of all employees. Improvement to the working conditions is done in order to please employees and employees feel happy with the job with the work gained as well as other facilities that support work activities. Thus, employees can work passionately, productively, and perform at their best.